The unique social sense of puerperium: Increased empathy and Schadenfreude in parents of newborns (2020)
Pregnancy and puerperium are typified by marked biobehavioral changes. These changes, which are traceable in both mothers and fathers, play an important role in parenthood and may modulate social cognition abilities. However, the latter effects remain notably unexplored in parents of newborns (PNs). To bridge this gap, we assessed empathy and social emotions (envy and Schadenfreude) in 55 PNs and 60 controls (childless healthy participants without a romantic relationship or sexual intercourse in the previous 48 hours). We used facial electromyography to detect physiological signatures of social emotion processing. Results revealed higher levels of affective empathy and Schadenfreude in PNs, the latter pattern being accompanied by increased activity of the corrugator suppercilii region. These effects were not explained by potential confounding variables (educational level, executive functioning, depression, stress levels, hours of sleep). Our novel findings suggest that PNs might show social cognition changes crucial for parental bonding and newborn care. © 2020, The Author(s).